Inovasi penanaman Seledri (Apium Graveolens L.) dengan teknik Low Capital and High Benefit di Desa Sumbersari - Darmawati Darmawati; Eko Purnomo (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
The celery plant is used as a food additive and in traditional medicine. Its high benefits allow for high market demand as well. Until now, in North Maluku, there has been no extensive cultivation of celery. On average, it only uses hydroponics and polybags even though the area of agricultural land is enormous, especially in Sumbersari village. The Low Capital and High Benefit technique use a basic farming system approach: planting directly into the ground. This PKM aims to provide a new understanding to the community about celery cultivation through direct planting techniques with a Low Capital and High Benefit approach so that the socio-economic partners better. This service location was in Sumbersari Village, Central Halmahera Regency, on August 18, 2022. The methods used were lectures, discussions, and demonstrations. The results of the service show that this service was successful. During socialization, the whole community was enthusiastic and could fully follow the material, which can be seen from the implementation when the success of celery cultivation reached 90%.